Metode Flipped Classroom Terhadap Motivasi Belajar Siswa Pada Materi Media Digital - Risma Wiwita; Revi Handayani; Riska Mayeni (Kilau Publishing, 2025)
This research is motivated by a decrease in student learning motivation at SMP DM Padang in grade IX. This decrease in student learning motivation shows that students are not enthusiastic when learning, feel bored, sleep in class and even often come and go to class. This study aims to determine the effect of the application of the Flipped Classroom learning method on student learning motivation in informatics subjects for grade IX at SMP DM Padang. The research method used is an experiment with a Nonoquevalent Control Group Design, which involves two groups, namely the experimental class given treatment using the Flipped Classroom method and the control class using the Conventional method. The data collection instrument is a questionnaire with a Likert Scale that has been tested for validity and reliability. Data analysis is carried out through normality tests, homogeneity tests, and hypothesis testing with t-tests. The results of the study show that the average value of the experimental class is higher than the control class, with a significance value below a = 0.05 so that the alternative hypothesis is accepted. This indicates a significant effect of the flipped classroom implementation on improving student learning motivation. This learning model can make students more active, independent, and engaged in the learning process, as well as increasing interaction between teachers and students. Thus, the flipped classroom can be an effective alternative learning strategy in the context of informatics education at the junior high school level. Therefore, this method is recommended as an effective learning alternative to increase student participation and enthusiasm for learning, especially in informatics subject